Nanomaterials in Drug Delivery, Imaging, and Tissue Engineering 2013
DOI: 10.1002/9781118644591.ch15
|View full text |Cite
|
Sign up to set email alerts
|

Core‐Sheath Fibers for Regenerative Medicine

Abstract: The history of fibers in biomedical sciences is not novel. However, the discovery of degradable polymers and advancement in fiber formation technology has ameliorated the regenerative medicine. Fiber-coated implants, synthetic sutures, and tissue engineering scaffolds are some of the best examples of biomedical fiber technology. In the last two decades, electrospinning has emerged as one of the potential techniques for large-scale production of nanofibers. Because of their inherent appearance similar to the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 128 publications
(181 reference statements)
0
1
0
Order By: Relevance
“…When the charge accumulation reaches a threshold, a jet emerges from the tip of the deformed droplet directed towards the counter electrode. Finally, a core-shell fiber is deposited on the substrate [56]. Recently, Hai et al [57] have reported the process of Taylor cone formation in typical one-fluid electrospinning and coaxial electrospinning processes; the digital photographic observations from their study are given in Figure 4.…”
Section: Core-sheath Nanofibersmentioning
confidence: 99%
“…When the charge accumulation reaches a threshold, a jet emerges from the tip of the deformed droplet directed towards the counter electrode. Finally, a core-shell fiber is deposited on the substrate [56]. Recently, Hai et al [57] have reported the process of Taylor cone formation in typical one-fluid electrospinning and coaxial electrospinning processes; the digital photographic observations from their study are given in Figure 4.…”
Section: Core-sheath Nanofibersmentioning
confidence: 99%